2023
DOI: 10.1039/d3cc00185g
|View full text |Cite
|
Sign up to set email alerts
|

On-surface synthesis of metal–organic frameworks: the critical role of the reaction conditions

Abstract: We have grown two different metal-organic frameworks with either honeycomb or Kagome structure on Cu(111) using para-aminophenol molecules and native surface adatoms. Although structurally different, both frameworks are made up...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The network structure formed by para -aminophenol molecules on Cu(111) surface could be adjusted to Kagome or honeycomb lattice through a kinetic or thermodynamically controlled reaction ( Figures 8 A and 8B). 82 The optimized network structure revealed that coordination bonds formed between N/O atoms and Cu atoms dominated the establishment of SMOF ( Figures 8 C and 8D). The oxidation process of precursor molecules on the surface was completely dependent on the final temperature (thermodynamics).…”
Section: Substrate−assisted Smofs Constructionmentioning
confidence: 97%
See 1 more Smart Citation
“…The network structure formed by para -aminophenol molecules on Cu(111) surface could be adjusted to Kagome or honeycomb lattice through a kinetic or thermodynamically controlled reaction ( Figures 8 A and 8B). 82 The optimized network structure revealed that coordination bonds formed between N/O atoms and Cu atoms dominated the establishment of SMOF ( Figures 8 C and 8D). The oxidation process of precursor molecules on the surface was completely dependent on the final temperature (thermodynamics).…”
Section: Substrate−assisted Smofs Constructionmentioning
confidence: 97%
“…Figures reproduced from: Ruiz et al. 82 Copyright 2023 Royal Society of Chemistry. (E) STM image of molecules deposition onto Cu(100) surface held at RT, followed by annealing at 370 K. (F) STM image of an isolated domain.…”
Section: Substrate−assisted Smofs Constructionmentioning
confidence: 99%
“…Crucially, 2D MONs having heterogeneous coordination nodes (HCNs) are expected to exhibit excellent performance in many fields such as catalysis and optoelectronics because the heterogeneous nature of metal coordination nodes may induce dipole and spin polarization as a result of the locally unbalanced electron distribution. For example, Lopez et al synthesized a Kagome MON composed of N 2 -Cu-O 2 nodes on Cu(111), and Abel et al constructed a 2D MON with O 3 -Fe-N nodes on Ag(111) . In contrast, Wu et al reported a binodal 2D organometallic network composed of both CC–Ag–CC and CC–Ag–phenyl nodes, whose synthesis involves a dissymmetric reaction of a terminal alkyne and bromobenzene on Ag(111) .…”
mentioning
confidence: 99%